Can Research on the Genetics of Intelligence Be “Socially Neutral”? - Roberts, Dorothy (The Hastings Center report, 2015)
The history of research on the genetics of intelligence is fraught with social bias. During the eugenics era, the hereditary theory of intelligence justified policies that encouraged the proliferation of favored races and coercively stemmed procreation by disfavored ones. In the 1970s, Berkeley psychologist Arthur Jensen argued that black students’ innate cognitive inferiority limited the efficacy of federal education programs. The 1994 controversial bestseller The Bell Curve, by Richard J. Herrnstein and Charles Murray, rehashed the claim that race and class disparities stem from immutable differences in inherited intelligence, which could not be eliminated through social interventions. Today most scientists studying the genetics of intelligence distance themselves from this history of social bias by arguing that their research need not investigate intellectual differences between social groups. Rather, they argue, examining the heritability of intelligence can be socially neutral and may even help to reduce social inequities. I argue, however, that research on the genetics of intelligence cannot be socially neutral. Even if we divorce the heritability of intelligence from a eugenicist mission, measuring intelligence remains useful only as a gage of individuals’ appropriate positions in society. Research into the genetics of intelligence ultimately helps to determine individuals’ inherited capacity for particular social positions, even when researchers aim to modify the effects of inheritance.